2021
DOI: 10.1093/mnras/stab3382
|View full text |Cite
|
Sign up to set email alerts
|

Stellar populations in local AGNs: evidence for enhanced star formation in the inner 100 pc

Abstract: In modern models and simulations of galactic evolution, the star formation in massive galaxies is regulated by an ad hoc active galactic nuclei (AGN) feedback process. However, the physics and the extension of such effects on the star formation history of galaxies is matter of vivid debate. In order to shed some light in the AGN effects over the star formation, we analyzed the inner 500×500 pc of a sample of 14 Seyfert galaxies using GMOS and MUSE integral field spectroscopy. We fitted the continuum spectra in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 81 publications
(98 reference statements)
2
6
0
Order By: Relevance
“…We found average age uncertainties in analysed AGN (non-AGN) of 2% (3%), 3% (5%) and 3% (4%) in the case of the young, intermediate, and old ages, respectively. We found that obtained average uncertainties are in line with previous studies (e.g., Cid Fernandes et al 2014;Burtscher et al 2021;Dahmer-Hahn et al 2022). The measured averaged uncertainties are included in Figure 3.…”
Section: Stellar Populations Of Fir Agn and Fir Non-agn Green Valley ...supporting
confidence: 92%
See 1 more Smart Citation
“…We found average age uncertainties in analysed AGN (non-AGN) of 2% (3%), 3% (5%) and 3% (4%) in the case of the young, intermediate, and old ages, respectively. We found that obtained average uncertainties are in line with previous studies (e.g., Cid Fernandes et al 2014;Burtscher et al 2021;Dahmer-Hahn et al 2022). The measured averaged uncertainties are included in Figure 3.…”
Section: Stellar Populations Of Fir Agn and Fir Non-agn Green Valley ...supporting
confidence: 92%
“…These identified the dominance of the older stellar populations (e.g. Lotz et al 2000;Renzini 2006;Gargiulo et al 2012;Sil'chenko et al 2012;Dahmer-Hahn et al 2018;Ferré-Mateu et al 2019;Lonoce et al 2020;Zibetti et al 2020;Dahmer-Hahn et al 2022), which had a total metallicity between less than half-solar to higher values (e.g. Lotz et al 2000;Lonoce et al 2020;Zibetti et al 2020) and enhanced α-elements over iron (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Another difference between our results and theirs is the fact that in all their AGNs except one, the light is dominated by old SPs, whereas this is the case for only two of our galaxies (NGC 3227 and NGC 5548). A similar analysis was done by Dahmer-Hahn et al (2021), who analyzed the stellar populations using optical IFU data of 14 AGN (being the optical counterpart of the present sample). Similarly to the results of Burtscher et al (2021), nine of their objects have evidence of young SPs in the inner 150 pc, with an average light contribution of 7 %.…”
Section: Discussionmentioning
confidence: 71%
“…The one possible exception to this rather boring normality is that a number of groups have found evidence that the star formation rate in the immediate vicinity of the AGN is often elevated [48,56,67,340].…”
Section: Star Formationmentioning
confidence: 99%